Motivasi Pengusaha Dalam Pengembangan Inovasi Produk (Penelitian Deskriptif Terhadap Pengusaha Garmen Muslim di Gresik) - Imanda, Ramadhany (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
Motivation is an effort to push or move in order to reach goals based on its ability to satisfy theÂ needs. Motivation of entrepreneurship in Islam is to work for a living as a duty to serve Allah SWTÂ and someoneâs heart level that motivates him/her into act based on Islamic dogma.Â Entrepreneurs put those Islamic religion aspects as prove that him/her is loyal to Allah SWT whichis arise because of the right intention, way and purpose to fulfill needs and performanceâsÂ improvement.This researchâs aim is to find out the motivation of Moslem garment entrepreneur at Gresik intoÂ developing product innovation. This research is using qualitative approach with descriptiveÂ study, data are collected by a direct observation, interview and documentation toward MoslemÂ garment entrepreneur at Gresik market region. Besides literature research which related toÂ Islamic motivation and product innovation also needed.The result shows that Moslem garment entrepreneur at Gresik has motivated until appropiateÂ teaching of entrepreneurship and Islamic jurisprudence to work independently in a living,Â working with an intention to worship Allah SWT. The motivation of the Moslem garmentÂ entrepreneur in Gresik try to do development of product innovation by doing modification andÂ produce the Moslemâs garment which likeable by their consumer, develop the market segment,Â also fix their product to escalate the product quality and give some added value.